Multifrecuency bioimpedance phase angle as a tool to predict maturation failure of native fistulae for hemodialysis - Lopez, José Lucas Daza; Galindo, John F; Villaquiran, Mónica R; Valenzuela, Emilio D; Cardenas, Andres; Daza, Luis Jose; Correcha, Maria Camila; Jong, Jonathan de; Prieto, Yaroslad De La Cruz; Gutierrez, Gerardo; et al. (Journal of Clinical Nephrology, 2021)
Background and objectives: An arteriovenous fistula is considered to be an ideal vascular access for patients receiving hemodialysis, its main limitation is its high failure rate to achieve maturation and long-term functionality loss. Multiple strategies have attempted to identify patients at risk. Bioelectrical impedance has shown to be a valuable resource in the determination of the hydration status, and the measurement of the phase angle through this method has demonstrated to be a good indicator of the nutritional state and its related as a general marker of survival. The objective of this study is to analyze the role of plasma albumin and phase angle measured through bioelectrical impedance as tools useful for predicting failure of arteriovenous fistulas. Materials and methods: prospective observational study, including 104 patients with chronic kidney disease receiving hemodialysis who underwent a native arteriovenous fistula during a period of 24 months. Analyzing its clinical characteristics, laboratory and phase angle through electrical bioimpedance, both univariate and multivariate analysis was performed both with logistic regression, furthermore calculation of coordinates and ROC curve to establish a better cut-off point. Results: of the variables that were analyzed only the phase angle measurement showed statistical significance OR 2.61 (1.6 – 4.4) p - value 0.001 for predicting arteriovenous fistula failure. In female patients with a phase angle value of 3.25 had a 90% sensibility and 53% specificity for male patients a value of 3.58 showed a sensibility of 84% and a specificity of 52% with ROC curve of 0.78. Conclusion: phase angle through bioimpedance is a useful parameter, helpful in predicting failure of native arteriovenous fistula, it is also an important tool for identifying patients at risk, in early stages prior to the construction of a vascular access.